Solve the equation. (Enter your answers as a comma-separated list. If there is no solution, enter NO SOLU X = 6 X = -x + 6 = x - 6 Identify any extraneous solution. (If there is no extraneous solution, enter NO SOLUTION.) 2
![Solve the equation Enter your answers as a commaseparated list If there is no solution enter NO SOLU X 6 X x 6 x 6 Identify any extraneous solution If there is class=](https://us-static.z-dn.net/files/dd9/16bd53c5688e690ebf205d6dee5b322c.jpg)
Taking squares on both sides leads to
[tex]\sqrt{-x + 6} = x - 6[/tex]
[tex]\left(\sqrt{-x + 6}\right)^2 = (x - 6)^2[/tex]
[tex]-x + 6 = x^2 - 12x + 36[/tex]
[tex]x^2 - 11x + 30 = 0[/tex]
[tex](x - 5) (x - 6) = 0[/tex]
Solving for [tex]x[/tex], we get
[tex]x - 5 = 0 \text{ or } x - 6 = 0[/tex]
or
[tex]x = 5 \text{ or } x = 6[/tex].
Evaluating both sides of the starting equation at these solutions, we have
[tex]\sqrt{-6 + 6} = 6 - 6 \implies 0 = 0[/tex]
which is true, so [tex]\boxed{x=6}[/tex] is a valid solution. However,
[tex]\sqrt{-5 + 6} = 5 - 6 \implies \sqrt1 = -1 \implies 1 = -1[/tex]
which is not true, so [tex]\boxed{x=5}[/tex] is an extraneous solution.